I racconti votivi contemporanei: pagine di un continuo liber miraculorum - Vincenzo Spera (EtnoAntropologia)
The article is based on documentations collected in field research conducted in sanctuaries and places of worship in South and Central Italy, since the early Seventies of last century until the first decade of the present one. The article presents an interpretation of the ex voto like a kind of storytelling of the experience lived by the devotee who claims to have had contact with the powerful Otherness. These votive tales, packed with painted images, photos, installations of various materials, written texts, are compared to the hagiographies of the Saints and exemplary stories which the devotee takes as specimen to present and tell publicly his own story of suffering and salvation.